Urinary Incontinence Associated with Sertraline use in a Young SSRI-Naí¯ve Female Patient: a Case Report - Anna Elissa (Jurnal Psikiatri Surabaya, 2024)
Introductions: Urinary incontinence is a side effect of several antidepressants, especially those in the SSRI and SNRI groups. Sertraline, a popular SSRI effective against a wide range of mental disorders, is one such drug with a clear association with a new onset of UI. Case: A 20-year-old Indonesian Chinese woman, presenting with mixed anxiety and depressive symptoms, was initially treated with sertraline 50 mg. She experienced an acute onset of urinary urgency and a loss of bladder control. These symptoms resolved upon discontinuation of sertraline. She was then given 10 mg of fluoxetine, and she noted that the urinary problems did not return. The medication was gradually tapered up to 40 mg/day with no remarkable adverse events. Discussions: Sertraline tends to stimulate micturition through effects on M3 muscarinic receptors on the bladder's detrusor muscle and inhibition of the dopamine transporter in the central nervous system. On the other hand, fluoxetine acts antagonistically on 5-HT2C, inhibiting the voiding reflex and promoting urinary continence. Therefore, though both are SSRIs, sertraline and fluoxetine may exhibit different, clinically meaningful effects. Conclusions: Clinicians need to have a greater awareness of urinary incontinence as a side effect of sertraline, as it impacts patients' adherence and quality of life. When possible, switching to fluoxetine is recommended for patients with urinary problems in the event of sertraline use.